Od Baali do Baala: Z problematyki badań nad koncepcją zachodniosemickiego boga burzy - Cinal, Stanisław
From Baals to Baal: On the Problems Related to the Study on the Conception of the West-Semitic Thunder- and Weather-God; anhand ugaritischer Texte.